MOBILITAS SOSIAL EKONOMI MIGRAN (PADA MIGRAN DI KELURAHAN TUAH NEGERI KECAMATAN TENAYAN RAYA) - Angriani, Tika; ", Risdayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The background of this research is based from the author's observation of Tuah Negeri Sub District which has only been developed in recent years, the area that used to be the forest now occupied by the migrants due to the rich natural conditions such as the bedeng soil, there are still many empty land that is currently established large factories, offices, oil palm plantations, etc., cause to be a place to migrate,because of many jobs. The problems that the author raises is the job mobility from before becoming a migrant and after becoming a migrant in Tuah Negeri Sub District. The formulation in this study is what factors affect the mobility and how the form of that mobility. Informants in this study is 8 (eight) persons who have become migrants for 10 years and above, the author take informants who have become migrants for 10 years and over because can be seen from their income, form their house and investment. The analysis used is descriptive qualitative method. The results of this study shows that from 8 informants,only 7 of them changed his job after becoming a migrant in Tuah Negeri Sub District. This happens because many factors, among them are economic factors. Not all informants changed after becoming migrant in Tuah Negeri Sub District, from 8 informants theres only 6 informants who experienced social climbing mobility and 2 other informants experienced social sinking mobility.Keywords: Mobility, Migrant, Economy